An Expert Guide to Anatomy-Based Filler Injection for the Temple: Techniques and Clinical Insights - Hong, Gi-Woong; Wan, Jovian; Choi, Wonseok; Yi, Kyu-Ho (Life (Basel, Switzerland), 2025)
Temporal hollowing is a common aesthetic concern addressed with filler injections using an anatomy-based approach. Understanding the complex anatomy of the temporal region, including the superficial temporal artery, temporal branch of the facial nerve, and sentinel vein, is essential for safe and effective treatment. Injection planes—subfascial, within the superficial temporal fat pad, or submuscular—are selected based on individual anatomy and desired outcomes. Techniques like retrograde horizontal fanning with a cannula optimize filler distribution, enhance contour, and minimize complications. Recognizing zones of caution helps prevent vascular and nerve injuries. This approach allows clinicians to achieve natural, youthful fullness in the temples, improving overall facial aesthetics and patient satisfaction.